Project Based Learning Based on Basic Locomotor Movement Skills in Physical Education Learning - Nasrullah, Nasrullah; Irfan, Irfan; Ardiansyah, Anas (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to develop a Project Based Learning (PBL) model based on basic locomotor movement skills and evaluate its effectiveness in learning Physical Education in elementary schools. Materials and methods. The research method uses a Research and Development (R&D) approach with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research subjects were students of PUBLIC PRIMARY SCHOOL 11 Bima Citywith an initial test involving 20 students and a final test involving 40 students. The measurement instrument for basic locomotor movement skills used the Test of Gross Motor Development (TGMD), including running, jumping, and hopping skills. Data were collected through observation, interviews, and tests, then analyzed qualitatively and quantitatively using the t-test, N-Gain, and Aiken's V validation. Results. The results of the study showed a significant increase in students' abilities after the implementation of the model. The average pretest score (cognitive 66.5; affective 66.8; psychomotor 68.0) increased in the posttest (cognitive 85.3; affective 86.0; psychomotor 88.5). The t-test obtained a value of 30.51 with p = 0.000 (<0.05), N-Gain of 58.18% was in the medium to high category, and Aiken's V validation showed very valid criteria (0.89–0.94). Conclusion: The findings show that integrating TGMD into the PBL framework effectively improves locomotor skills, active participation, motivation, and collaboration, thereby supporting holistic development and enhancing the quality of physical education learning.